Optimal design and experimental research of vehicle suspension based on a hydraulic electric inerter. (August 2019) - Shen, Yujie; Liu, Yanling; Chen, Long; Yang, Xiaofeng
Abstract: As the mechanical dual of a capacitor via the force-current analogy, an inerter has been successfully applied in various fields such as automotive engineering, civil engineering and aerospace engineering. The introduction of an inerter not only allows the use of network synthesis analogy to design mechanical layouts but also opens the door to adopt electrical element impedances to simulate the corresponding mechanical elements. This paper combines both of these ideas and presents a new form of a mechatronic inerter, namely the hydraulic electric inerter (HEI), which consists of a hydraulic piston inerter and a linear motor. On the basis of the HEI device, a bicubic impedance function is considered in the optimal design of a vehicle suspension system employing both mechanical elements and electrical elements. In addition, a methodology for reducing the order of the bicubic impedance function is proposed, and the network is finally realized by utilizing inerter, spring and damper elements. Then, by comparison with a passive suspension, the advantages of the new vehicle ISD (inerter-spring-damper) suspension, called the vehicle HE-ISD (hydraulic electric-inerter spring damper) suspension, are demonstrated by numerical simulations. Finally, a HEI device is designed, and bench tests of the vehicle HE-ISD suspension are carried out. Experimental results indicate that, the vehicle HE-ISD suspension is superior to the passive suspension system, the RMS (root-mean-square) value of the suspension working space is improved by 19.97%, and the RMS value of the dynamic tire load is improved by 10.21%.